A multi-shell structure CO-SCR denitration catalyst and preparation method thereof
By self-assemblying layer by layer to form a multi-shell structure, the problem of insufficient low-temperature activity in the prior art under oxygen-rich conditions is solved, efficient NOx conversion and good N2 selectivity are achieved, and preparation is reduced cost.
Patent Information
- Application Number
- CN202211606544.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The existing CO-SCR denitrification catalysts are insufficient in low-temperature activity under oxygen-rich conditions, and the preparation method is high in cost and poor structural controllability, making it difficult to meet the needs of industrial applications.
By self-assembling layer by layer, forming a CO-SCR denitrification catalyst with a multi-shell structure, using carbon spheres as templates, prepared through hydrothermal treatment and stepwise precipitation process, a uniform mesoporous structure and a combination of multiple metal oxides are formed to improve catalytic activity and Antioxidant properties.
Highly efficient NOx conversion and good N2 selectivity under low temperature and oxygen-rich conditions are achieved, reducing the preparation cost and improving the uniformity and controllability of the catalyst.
Smart Images

Figure CN115999543B_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present invention relate to the technical field of denitration catalysts, and in particular to a multi-shell structure CO-SCR denitration catalyst and a preparation method thereof. Background Art
[0002] CO and NO x It is a typical atmospheric pollutant from motor vehicle exhaust, coal-fired power plants and industrial sources (steel, coking, cement and ceramic industries). The selective catalytic reduction of NO by CO (CO-SCR) is a synergistic removal of CO and NO. x At the same time, the heat generated by CO oxidation can be used to provide CO denitration reaction, thereby saving energy and reducing carbon emissions. However, an important issue in the CO-SCR reaction is that the catalytic activity will be severely reduced in the presence of O2. Therefore, the development of low-cost, high-performance CO-SCR denitration catalysts under oxygen-rich conditions is the core of this technology.
[0003] In recent years, low-cost CO-SCR catalysts suitable for oxygen-containing conditions have been reported, such as MnO x ,FeO x, CuO, CeO2 and Co3O4, etc. Wen et al. (Journal of Molecular Catalysis A: Chemical, 2002, 180 (1 / 2): 187-192.) found that when the volume fraction of O2 in the system was 0.5% (O2 / CO = 0.36), the NO conversion rate of Cu-Ce catalyst at 315°C could reach 100%. Zeng et al. (Industrial & Engineering Chemistry Research, 2020, 59 (1): 34-41.) reported that Co3O4 / CeO2 catalyst showed high activity in the presence of 2% O2 due to its excellent reduction performance and rich chemically adsorbed oxygen. Li et al. (Journal of Hazardous Materials, 2022, 431: 128622.) Ni-doped Fe / CeO2 catalyst achieved 100% NO conversion at 250°C under 0.5% O2 due to its rich surface synergistic oxygen vacancies. Pan et al. (Catalysis Today, 2019, 348.) prepared Cu-Ce-Fe-Co / TiO2 catalyst by impregnation method. Under 6% O2 condition, the NO conversion rate was 63% at 200℃. Fu Yuxiu et al. (China Environmental Science, 2018, 38(8): 2934-2940.) studied the Ce-Co binary composite metal oxide catalyst with Ce:CO=3:7 under the system of O2 volume fraction of 5% and CO:NO=2:1. The highest NO conversion rate was 84% (250℃). Li et al. (Chemical Engineering Journal, 2014, 255: 126-133.) investigated the effect of O2 concentration on Fe-based catalyst CO-SCR and found that the NO conversion rate was 100% at 700°C without O2, and the NO conversion rate dropped to 55% with O2 (O2 / CO = 0.4). If the O2 concentration is further increased (O2 / CO ≥ 0.4), the NO conversion rate drops sharply to 0%. Liu et al. proposed Cu 1.2 FeMg 2.8 -LDO reached 100% NO conversion at 225℃ under anaerobic conditions. After 1% O2 was introduced, the NO conversion rate gradually dropped to 0% after 1 hour.
[0004] However, there are still some problems in the research of the above denitration catalysts, including low applicable oxygen concentration, low low-temperature NO conversion rate, poor N2 selectivity, or large pollution and toxicity in preparation. At present, there are few preparation methods for low-temperature denitration catalysts for CO-SCR reaction under oxygen-rich conditions using non-precious metals. Therefore, the development of a denitration catalyst catalyzed by a cheap transition metal is of great significance for the industrial application of CO-SCR reaction under oxygen-rich conditions. Summary of the invention
[0005] To this end, an embodiment of the present invention provides a method for preparing a multi-shell structure CO-SCR denitration catalyst.
[0006] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:
[0007] According to a first aspect of an embodiment of the present invention, an embodiment of the present invention provides a method for preparing a multi-shell structure CO-SCR denitration catalyst, comprising:
[0008] The carbon source is subjected to hydrothermal treatment to obtain carbon spheres;
[0009] The carbon sphere is used as a template and the metal salt is used as an active raw material, and a multi-shell precursor is obtained through a stepwise precipitation process;
[0010] The multi-shell precursor is calcined to obtain the CO-SCR denitration catalyst.
[0011] The multi-shell structure formed by layer-by-layer self-assembly of the present invention has a uniform mesopore distribution, which is conducive to the diffusion of small gas molecules. In addition, the multi-shell structure can improve the heterojunction interaction between oxides. As a CO-SCR denitrification catalyst, it can effectively regulate the electronic structure on the catalytic active site, thereby selectively adsorbing different gas reactants, and achieving good low-temperature activity and anti-oxidation, SO2 and H2O performance. The preparation method of the catalyst is low in cost, strong in structural controllability, and high in uniformity of the synthesized catalyst.
[0012] Furthermore, the multi-shell structure comprises at least two cavities and at least two layers of shell walls, and the multi-shell structure contains at least two or more metal oxides, preferably two shells or three shells.
[0013] Furthermore, the carbon source is selected from any one or a combination of two of sucrose, glucose, fructose, maltose, starch or citric acid.
[0014] Furthermore, the hydrothermal treatment includes: preparing the carbon source into a 0.1-0.4M aqueous solution, placing it in a high-pressure reactor, hydrothermally reacting at 150-250°C for 2-10 hours, collecting the solid after cooling, and drying it at 60-120°C to obtain the carbon spheres.
[0015] Furthermore, the metal salt includes a combination of at least any two of copper salt, iron salt, manganese salt, cobalt salt or cerium salt.
[0016] Furthermore, the copper salt is selected from any one of copper nitrate, copper sulfate, copper chloride or copper acetate, or a combination of at least two thereof, preferably copper nitrate or copper acetate.
[0017] Further, the iron salt is selected from any one or a combination of at least two of ferric nitrate, ferric sulfate, ferric chloride or ferric acetate, preferably ferric nitrate or acetic acid;
[0018] Furthermore, the manganese salt is selected from any one or a combination of at least two of manganese nitrate, manganese sulfate, manganese chloride or manganese acetate.
[0019] Furthermore, the cobalt salt is selected from any one of cobalt nitrate, cobalt sulfate, cobalt chloride or cobalt acetate, or a combination of at least two thereof.
[0020] Furthermore, the cerium salt is selected from any one of cerium nitrate, cerium sulfate, cerium chloride or cerium acetate, or a combination of at least two thereof.
[0021] Furthermore, the molar content of the copper salt in the metal salt is 10% to 90%, preferably 40% to 60%.
[0022] Furthermore, the molar content of the iron salt in the metal salt is 10% to 90%, preferably 40% to 60%.
[0023] Furthermore, the molar content of the manganese salt in the metal salt is 10% to 90%, preferably 40% to 60%.
[0024] Furthermore, the molar content of the cobalt salt in the metal salt is 10% to 90%, preferably 40% to 60%.
[0025] Furthermore, the molar content of the cerium salt in the metal salt is 10% to 90%, preferably 40% to 60%.
[0026] Further, the stepwise precipitation process comprises:
[0027] Dissolve a portion of the metal salt in water to prepare a metal salt aqueous solution, add carbon spheres, stir for 0.5 to 2 hours, add a precipitant until the solution pH is 7 to 10, stir for 0.1 to 2 hours, heat to 50 to 100° C., stir for 1 to 10 hours, and filter to obtain a layer of precursor with carbon spheres as templates;
[0028] Another part of the metal salt is dissolved in water to prepare a metal salt aqueous solution, a layer of precursor is added, and the precipitation process is repeated to obtain a multi-shell precursor.
[0029] Furthermore, the concentration of the metal salt aqueous solution is 0.001 to 0.8 mol / L, preferably 0.01 to 0.4 mol / L.
[0030] Furthermore, the precipitant is selected from any one of sodium hydroxide, sodium carbonate, potassium carbonate, ammonia water or urea, or a combination of at least two thereof.
[0031] Furthermore, the precipitant is prepared into an aqueous solution with a concentration of 0.5 to 5 mol / L.
[0032] Furthermore, the calcination treatment is carried out at a temperature of 400 to 600° C. and for a time of 2 to 8 hours.
[0033] Furthermore, before the calcination step, the method further comprises: drying the multi-shell precursor to obtain a multi-shell metal oxide; the drying temperature is 60-120°C.
[0034] According to a second aspect of an embodiment of the present invention, an embodiment of the present invention provides a CO-SCR denitration catalyst prepared by the method described in any one of the above items.
[0035] The embodiments of the present invention have the following advantages:
[0036] (1) The present invention improves the heterojunction interaction between oxides by forming a multi-shell structure through layer-by-layer self-assembly, effectively regulates the electronic structure at the catalytic active site, thereby selectively adsorbing different gas reactants, achieving good low-temperature activity and resistance to oxygen, SO2 and H2O.
[0037] (2) The shell structure formed by layer-by-layer self-assembly of the present invention has a uniform mesopore distribution, which is beneficial to the diffusion of small gas molecules and has a significant promoting effect on the low-temperature catalytic performance of the CO-SCR reaction.
[0038] (3) The preparation method provided by the present invention has low cost, strong structural controllability and high uniformity of the synthesized catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. Obviously, the drawings in the following description are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.
[0040] Figure 1 This is the XRD diagram of the CO-SCR denitration catalyst provided in Example 5 of the present invention. DETAILED DESCRIPTION
[0041] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] This embodiment provides a multi-shell structure CO-SCR denitration catalyst, and the preparation method thereof is as follows:
[0044] (1) Glucose was prepared into a 0.12 M aqueous solution, and subjected to hydrothermal reaction at 180° C. in a high-pressure reactor for 5 hours. After cooling, the solid was collected by filtration and dried at 100° C. for 3 hours to obtain carbon spheres.
[0045] (2) Prepare 0.04 mol of copper nitrate, 0.04 mol of iron nitrate, and 0.06 mol of carbon spheres.
[0046] (3) Dissolve copper nitrate and carbon spheres in 1000 mL of water, stir for 1 hour, add 1 mol / L urea solution until the solution pH is 7, stir for 1 hour, heat to 90°C, continue stirring for 5 hours, and filter to obtain a layer of precursor. Add a layer of precursor and iron nitrate to 1000 mL of water, stir for 1 hour, add 1 mol / L urea solution until the solution pH is 7, stir for 1 hour, heat to 90°C, continue stirring for 5 hours, and filter to obtain a second layer of precursor.
[0047] (3) The two-layer precursor was dried at 100°C for 5 hours and calcined at 450°C for 3 hours to obtain a Fe@Cu two-shell CO-SCR denitrification catalyst.
[0048] Example 2
[0049] This embodiment provides a multi-shell structure CO-SCR denitration catalyst, and the preparation method thereof is as follows:
[0050] (1) Sucrose was prepared into a 0.1 M aqueous solution, and hydrothermally treated at 190° C. for 4 hours in a high-pressure reactor. After cooling, the solid was collected by filtration, and then dried at 110° C. for 3 hours to obtain carbon spheres.
[0051] (2) Prepare 0.04 mol of copper nitrate, 0.03 mol of manganese nitrate, and 0.06 mol of carbon spheres.
[0052] (3) Dissolve copper nitrate and carbon spheres in 1000 mL of water, stir for 0.5 hours, add 1.5 mol / L sodium carbonate solution until the pH of the solution is 7.5, stir for 1 hour, heat to 100°C, continue stirring for 4 hours, and filter to obtain a layer of precursor. Add a layer of precursor and manganese nitrate to 1000 mL of water, stir for 1 hour, add 1.5 mol / L sodium carbonate solution until the pH of the solution is 7.5, stir for 1 hour, heat to 100°C, continue stirring for 4 hours, and filter to obtain a second layer of precursor.
[0053] (4) The two-layer precursor was dried at 100°C for 6 hours and calcined at 500°C for 5 hours to obtain a Mn@Cu two-shell CO-SCR denitrification catalyst.
[0054] Example 3
[0055] This embodiment provides a multi-shell structure CO-SCR denitration catalyst, and the preparation method thereof is as follows:
[0056] (1) Citric acid was prepared into a 0.5 M aqueous solution, and hydrothermally treated at 190° C. for 4 hours in a high-pressure reactor. After cooling, the solid was collected by filtration, and dried at 110° C. for 3 hours to obtain carbon spheres.
[0057] (2) Prepare 0.01 mol of cobalt acetate, 0.009 mol of manganese acetate, and 0.015 mol of carbon spheres.
[0058] (3) Dissolve cobalt acetate and carbon spheres in 1000 mL of water at a molar ratio of 2:3, stir for 0.5 hours, add 2 mol / L potassium carbonate solution until the solution pH is 8, stir for 0.5 hours, heat to 100°C, continue stirring for 4 hours, and filter to obtain a layer of precursor. Add a layer of precursor and manganese acetate to 1000 mL of water, stir for 0.5 hours, add 2 mol / L potassium carbonate solution until the solution pH is 8, stir for 1 hour, heat to 100°C, continue stirring for 8 hours, and filter to obtain a second layer of precursor.
[0059] (4) The two-layer precursor was dried at 110°C for 5 hours and calcined at 500°C for 4 hours to obtain a Mn@Co two-shell CO-SCR denitrification catalyst.
[0060] Example 4
[0061] This embodiment provides a multi-shell structure CO-SCR denitration catalyst, and the preparation method thereof is as follows:
[0062] (1) Maltose was prepared into a 0.2 M aqueous solution, and hydrothermally treated at 220° C. for 5 hours in a high-pressure reactor. After cooling, the solid was collected by filtration, and dried at 120° C. for 2 hours to obtain carbon spheres.
[0063] (2) Prepare 0.2 mol of cobalt acetate, 0.22 mol of cerium acetate, and 0.3 mol of carbon spheres.
[0064] (3) Dissolve cobalt acetate and carbon spheres in 1000 mL of water, stir for 0.5 hours, add 2 mol / L potassium carbonate solution until the solution pH is 8, stir for 0.5 hours, heat to 100°C, continue stirring for 4 hours, and filter to obtain a layer of precursor. Add a layer of precursor and cerium acetate to 1000 mL of water, stir for 0.5 hours, add 1 mol / L sodium hydroxide solution until the solution pH is 7.5, stir for 1 hour, heat to 100°C, continue stirring for 8 hours, and filter to obtain a two-layer precursor.
[0065] (4) The two-layer precursor was dried at 100°C for 3 hours and calcined at 550°C for 5 hours to obtain a Ce@Co two-shell CO-SCR denitrification catalyst.
[0066] Example 5
[0067] This embodiment provides a multi-shell structure CO-SCR denitration catalyst, and the preparation method thereof is as follows:
[0068] (1) Glucose was prepared into a 0.35 M aqueous solution, and hydrothermally treated at 200° C. for 6 hours in a high-pressure reactor. After cooling, the solid was collected by filtration and dried at 110° C. for 2 hours to obtain carbon spheres.
[0069] (2) Prepare 0.08 mol of cerium nitrate, 0.002 mol of manganese nitrate, 0.08 mol of cobalt nitrate, and 0.12 mol of carbon spheres.
[0070] (3) Dissolve cerium nitrate and carbon spheres in 1000 mL of water, stir for 0.5 hours, add 1 mol / L ammonia solution until the solution pH is 7, stir for 1 hour, heat to 90°C, continue stirring for 8 hours, and filter to obtain a layer of precursor. Add a layer of precursor, manganese nitrate and cobalt nitrate to 1000 mL of water, stir for 0.5 hours, add 1 mol / L ammonia solution until the solution pH is 7, stir for 1 hour, heat to 90°C, continue stirring for 8 hours, and filter to obtain a second layer of precursor.
[0071] (4) The two-layer precursor was dried at 65°C for 6 hours and calcined at 550°C for 5 hours to obtain a Mn-Co@Ce two-shell CO-SCR denitrification catalyst.
[0072] Example 6
[0073] This embodiment provides a multi-shell structure CO-SCR denitration catalyst, and the preparation method thereof is as follows:
[0074] (1) Sucrose was prepared into a 0.3 M aqueous solution, and hydrothermally treated at 190° C. for 7 hours in a high-pressure reactor. After cooling, the solid was collected by filtration and dried at 100° C. for 2 hours to obtain carbon spheres.
[0075] (2) Prepare 0.05 mol of ferric chloride, 0.05 mol of copper nitrate, 0.05 mol of manganese acetate, and 0.075 mol of carbon spheres.
[0076] (3) Dissolve ferric chloride and carbon spheres in 1000 mL of water at a molar ratio of 2:3, stir for 0.5 hours, add 2 mol / L sodium carbonate solution until the solution pH is 7, stir for 0.5 hours, heat to 90°C, continue stirring for 6 hours, and filter to obtain a layer of precursor. Add the layer of precursor and copper nitrate to 1000 mL of water, stir for 0.5 hours, add 2 mol / L sodium carbonate solution until the solution pH is 10, stir for 0.5 hours, heat to 80°C, continue stirring for 6 hours, and filter to obtain a layer of precursor. Add the layer of precursor and manganese acetate to 1000 mL of water, stir for 0.5 hours, add 2 mol / L sodium carbonate solution until the solution pH is 10, stir for 0.5 hours, heat to 80°C, continue stirring for 6 hours, and filter to obtain a layer of precursor.
[0077] (4) The three-layer precursor was dried at 80°C for 4 hours and calcined at 500°C for 5 hours to obtain a Mn@Cu@Fe three-shell CO-SCR denitrification catalyst.
[0078] Example 7
[0079] The only difference between this embodiment and embodiment 1 is that in step (2), 0.06 mol of copper nitrate, 0.03 mol of ferric nitrate, and 0.09 mol of carbon spheres are used, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0080] Example 8
[0081] The only difference between this embodiment and embodiment 2 is that in step (2), 0.1 mol of copper nitrate, 0.05 mol of manganese nitrate, and 0.15 mol of carbon spheres are used, and the other conditions and parameters are exactly the same as those in embodiment 2.
[0082] Example 9
[0083] The only difference between this embodiment and embodiment 3 is that in step (2), 0.05 mol of cobalt acetate, 0.02 mol of manganese acetate, and 0.075 mol of carbon spheres are used, and the other conditions and parameters are exactly the same as those in embodiment 3.
[0084] Example 10
[0085] The only difference between this embodiment and embodiment 4 is that in step (2), 0.08 mol of cobalt acetate, 0.04 mol of cerium acetate, and 0.12 mol of carbon spheres are used, and the other conditions and parameters are exactly the same as those in embodiment 4.
[0086] Embodiment 11
[0087] The only difference between this embodiment and embodiment 5 is that in step (2), 0.05 mol of cerium nitrate, 0.001 mol of manganese nitrate, 0.1 mol of cobalt nitrate, and 0.075 mol of carbon spheres are used. Other conditions and parameters are exactly the same as those in embodiment 5.
[0088] Example 12
[0089] The only difference between this embodiment and embodiment 6 is that in step (2), 0.08 mol of ferric chloride, 0.05 mol of copper nitrate, 0.08 mol of manganese acetate, and 0.12 mol of carbon spheres are used. Other conditions and parameters are exactly the same as those in embodiment 6.
[0090] Comparative Example 1
[0091] This comparative example provides a catalyst, and its preparation method is as follows:
[0092] Cobalt nitrate and cerium nitrate were weighed and dissolved in water. The concentrations of cobalt nitrate and cerium nitrate were 0.2 mol / L and 0.22 mol / L, respectively. 1 mol / L potassium hydroxide solution was added until the pH of the solution reached 7.5. The solution was allowed to stand for 1 hour. After suction filtration and washing, it was dried at 100°C for 6 hours and calcined at 500°C for 5 hours to obtain a Co3O4-CeO2 catalyst.
[0093] Comparative Example 2
[0094] This comparative example provides a catalyst, and its preparation method is as follows:
[0095] Weigh ferric chloride and cupric chloride and dissolve them in water to a concentration of 0.04 mol / L and 0.04 mol / L, respectively. Add 1.5 mol / L urea solution until the pH value of the solution is 8. Let stand for 1 hour. After suction filtration and washing, dry at 80°C for 6 hours and calcine at 450°C for 5 hours to obtain a Fe2O3-CuO catalyst.
[0096] Comparative Example 3
[0097] This comparative example provides a catalyst, and its preparation method is as follows:
[0098] Weigh cerium nitrate, manganese nitrate and cobalt nitrate and dissolve them in water, the concentration of cerium nitrate is 0.08 mol / L, the concentration of manganese nitrate is 0.002 mol / L and the concentration of cobalt nitrate is 0.08 mol / L, add 1 mol / L ammonia solution until the pH of the solution is 7, let it stand for 1 hour, filter and wash, dry at 100°C for 6 hours, and calcine at 500°C for 5 hours to obtain CeO2-MnO2-Co3O4 catalyst.
[0099] Comparative Example 4
[0100] This comparative example provides a catalyst, and its preparation method is as follows:
[0101] Weigh ferric chloride, copper nitrate and manganese acetate and dissolve them in water to a concentration of 0.05 mol / L ferric chloride, 0.05 mol / L copper nitrate and 0.05 mol / L manganese acetate. Add 2 mol / L sodium carbonate solution until the solution pH is 7. Let stand for 1 hour. After suction filtration and washing, dry at 100°C for 6 hours and calcine at 500°C for 5 hours to obtain a Fe2O3-CuO-MnO2 catalyst.
[0102] Test Case
[0103] Performance Testing
[0104] The catalysts prepared in Examples 1 to 12 of the present invention and Comparative Examples 1 to 4 were subjected to the corresponding product indexes and CO selective catalytic reduction of NO x Performance measurement: It should be noted that in the above 12 embodiments, the tests were repeated three times in parallel, and the results were averaged.
[0105] A certain amount of quartz wool, 2 mL of quartz sand, and 3 mL of catalyst (20-40 mesh) are sequentially loaded into the reactor. The reaction gas and balance gas are introduced until adsorption is saturated. In the experiment of the influence of denitrification performance, the imported simulated flue gas volume is: CO = 2000ppm, NO = 1000ppm, O2 = 5%, N2 is the balance gas, and the air velocity is 20000h -1 , the total gas volume is 1L / min. NO conversion rate and NO2 selectivity are shown in equations (1)-(3) respectively:
[0106]
[0107]
[0108]
[0109] Note: [NO2] out : NO2 outlet concentration; [N2O] out : N2O outlet concentration; [NO2] in : Initial concentration of NO2; [NO]in : NO inlet concentration; [NO] out : NO outlet concentration; [CO] in : CO inlet concentration; [CO] out : CO outlet concentration.
[0110] In the experiment of the effect of denitration catalytic performance, the reaction was carried out at a temperature range of 100-400°C. The denitration catalytic performance data changing with temperature was recorded after being kept stable for 1 hour at each temperature point, and the performance at 200°C and 300°C were selected for comparison. The results are shown in Table 1.
[0111] Table 1
[0112]
[0113]
[0114] As can be seen from Table 1, the catalysts of Examples 1-12 can achieve a NO conversion rate of more than 48% and a N2 selectivity of more than 58% at 200°C, a NO conversion rate of more than 76% and a N2 selectivity of more than 50% at 300°C, and the catalytic activity is higher than that of Comparative Examples 1-4. By adjusting the shell composition, the NO conversion rate can reach 91% and the N2 selectivity can reach 89% at 300°C.
[0115] By comparing Examples 1-12, it can be seen that compared with catalyst samples without manganese, catalyst samples doped with manganese or as a shell have higher low-temperature activity (200°C) and NO conversion rate higher than 60%, indicating that manganese is beneficial to improving the low-temperature NO removal performance of the catalyst; compared with catalyst samples without cerium, samples doped with cerium or as a shell show better N2 selectivity (>80%), which is due to the abundant oxygen vacancies on the surface of cerium dioxide, which promotes the dissociation of nitrogen oxides. Compared with the two-shell structure, the three-shell structure catalyst has higher NO removal performance and N2 selectivity. The multi-shell structure is formed by layer-by-layer self-assembly to improve the heterojunction interaction between oxides, effectively regulate the electronic structure on the catalytic active site, especially the high-valence state (Mn 4+ , Mn 3+ 、Co 3+ and / or Fe 3+ ) ions, selective adsorption of different gas reactants to achieve good low-temperature activity.
[0116] In the catalyst denitrification anti-poisoning performance test experiment, the imported simulated flue gas volume: CO = 2000ppm, NO = 1000ppm, SO2 = 50ppm, H2O = 10%, O2 = 5%, N2 as the balance gas, and the air velocity is 20000h -1The total gas volume is 1L / min. The CO-SCR denitration reaction is carried out at a temperature of 250°C. The denitration catalytic performance data is recorded after stabilization every hour, and the average is 10 hours. The results are shown in Table 2.
[0117] Table 2
[0118]
[0119]
[0120] As can be seen from Table 2, when the heterogeneous structure contains cerium components, the multi-shell catalyst exhibits higher resistance to oxygen, SO2 and H2O (Table 2). Ceria has abundant surface lattice oxygen and oxygen vacancies, which is more conducive to the adsorption of SO2 and effectively inhibits the poisoning of catalytic active sites. Combined with the interaction between multiple components in the multi-shell structure, it exhibits good catalytic performance.
[0121] In summary, the CO-SCR denitration catalyst provided by the present invention is doped with a multi-shell structure catalyst, which contains a high-valent metal (Mn 4+ , Mn 3+ 、Co 3+ and / or Fe 3+ ) ions, the catalyst can achieve higher low-temperature activity. The catalyst containing the Ce shell shows excellent N2 selectivity. The synergistic effect between the three-shell multi-component can effectively regulate the adsorption capacity of the reactants, thereby achieving low-temperature activity and N2 selectivity regulation of the catalyst. Preferably, it contains Mn, Co, Cu and / or Ce components, wherein the high-valent metal exists in a doping or shell structure, and Cu and / or Ce exists in a shell structure.
[0122] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A method for preparing a multi-shell structure CO-SCR denitration catalyst, characterized in that: include: The carbon source is subjected to hydrothermal treatment to obtain carbon spheres; The carbon sphere is used as a template and the metal salt is used as an active raw material, and a multi-shell precursor is obtained through a stepwise precipitation process; calcining the multi-shell precursor to obtain the CO-SCR denitration catalyst; The metal salt is composed of manganese salt, cobalt salt and cerium salt, and the molar ratio of manganese salt, cobalt salt and cerium salt is 0.002:0.08:0.08 or 0.001:0.1:0.05; The stepwise precipitation process comprises: Dissolving a portion of the metal salt in water to prepare a metal salt aqueous solution, adding carbon spheres, stirring for 0.5 to 2 hours, adding a precipitant until the solution pH is 7 to 10, stirring for 0.1 to 2 hours, heating to 50 to 100° C., stirring for 1 to 10 hours, and filtering to obtain a layer of precursor with carbon spheres as templates; dissolving another portion of the metal salt in water to prepare a metal salt aqueous solution, adding a layer of precursor, and repeating the precipitation process to obtain a multi-shell precursor; The calcination temperature is 400-600°C and the calcination time is 2-8 hours.
2. The preparation method according to claim 1, characterized in that: The multi-shell structure comprises at least two cavities and at least two layers of shell walls, and the multi-shell structure contains at least two or more metal oxides.
3. The preparation method according to claim 1, characterized in that: The carbon source is selected from any one or a combination of two of sucrose, glucose, fructose, maltose, starch or citric acid.
4. The preparation method according to claim 1, characterized in that: The hydrothermal treatment comprises: preparing a carbon source into a 0.1-0.4M aqueous solution, placing the solution in a high pressure reactor, performing a hydrothermal reaction at 150-250° C. for 2-10 hours, collecting the solid after cooling, and drying the solid at 60-120° C. to obtain the carbon spheres.
5. The preparation method according to claim 1, characterized in that: The manganese salt is selected from any one or a combination of at least two of manganese nitrate, manganese sulfate, manganese chloride or manganese acetate; The cobalt salt is selected from any one of cobalt nitrate, cobalt sulfate, cobalt chloride or cobalt acetate, or a combination of at least two thereof; The cerium salt is selected from any one of cerium nitrate, cerium sulfate, cerium chloride or cerium acetate, or a combination of at least two thereof.
6. The preparation method according to claim 1, characterized in that: The concentration of the metal salt aqueous solution is 0.001-0.8 mol / L; And / or, the precipitant is selected from any one or a combination of at least two of sodium hydroxide, sodium carbonate, potassium carbonate, ammonia water or urea; And / or, the precipitant is prepared into an aqueous solution with a concentration of 0.5-5 mol / L.
7. The preparation method according to claim 6, characterized in that: The concentration of the metal salt aqueous solution is 0.01-0.4 mol / L.
8. The preparation method according to claim 1, characterized in that: Before the calcination step, the method further comprises: drying the multi-shell precursor to obtain a multi-shell metal oxide; the drying temperature is 60-120°C.
9. A CO-SCR denitration catalyst, characterized in that: Prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
CO-SCR denitration catalyst as well as preparation method and application thereof
CN111229212A